Racial and geographic variation in coronary heart disease mortality trends - Gillum Richard F; Mehari Alem; Curry Bryan; Obisesan Thomas O (BMC, 2012)
Abstract Background Magnitudes, geographic and racial variation in trends in coronary heart disease (CHD) mortality within the US require updating for health services and health disparities research. Therefore the aim of this study is to present data on these trends through 2007. Methods Data for CHD were analyzed using the US mortality files for 1999-2007 obtained from the US Centers for Disease Control and Prevention. Age-adjusted annual death rates were computed for non-Hispanic African Americans (AA) and European Americans (EA) aged 35-84 years. The direct method was used to standardize rates by age, using the 2000 US standard population. Joinpoint regression models were used to evaluate trends, expressed as annual percent change (APC). Results For both AA men and women the magnitude in CHD mortality is higher compared to EA men and women, respectively. Between 1999 and 2007 the rate declined both in AA and in EA of both sexes in every geographic division; however, relative declines varied. For example, among men, relative average annual declines ranged from 3.2% to 4.7% in AA and from 4.4% to 5.5% in EA among geographic divisions. In women, rates declined more in later years of the decade and in women over 54 years. In 2007, age-adjusted death rate per 100,000 for CHD ranged from 93 in EA women in New England to 345 in AA men in the East North Central division. In EA, areas near the Ohio and lower Mississippi Rivers had above average rates. Disparities in trends by urbanization level were also found. For AA in the East North Central division, the APC was similar in large central metro (−4.2), large fringe metro (−4.3), medium metro urbanization strata (−4.4), and small metro (−3.9). APC was somewhat higher in the micropolitan/non-metro (−5.3), and especially the non-core/non-metro (−6.5). For EA in the East South Central division, the APC was higher in large central metro (−5.3), large fringe metro (−4.3) and medium metro urbanization strata (−5.1) than in small metro (−3.8), micropolitan/non-metro (−4.0), and non-core/non-metro (−3.3) urbanization strata. Conclusions Between 1999 and 2007, the level and rate of decline in CHD mortality displayed persistent disparities. Declines were greater in EA than AA racial groups. Rates were greater in the Ohio and Mississippi River than other geographic regions.